2007
DOI: 10.1074/jbc.m706048200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Allosteric Substrate Activation in a Thiamine Diphosphate-dependent Decarboxylase

Abstract: Thiamine diphosphate-dependent enzymes are involved in a wide variety of metabolic pathways. The molecular mechanism behind active site communication and substrate activation, observed in some of these enzymes, has since long been an area of debate. Here, we report the crystal structures of a phenylpyruvate decarboxylase in complex with its substrates and a covalent reaction intermediate analogue. These structures reveal the regulatory site and unveil the mechanism of allosteric substrate activation. This sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…The enzyme encoded by the ipdC gene derived from Azospirillum brasilense has been extensively investigated, and its threedimensional structure has been published (35,42). The enzyme acts not only on PP but also on 4HPP to produce the corresponding aldehydes.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme encoded by the ipdC gene derived from Azospirillum brasilense has been extensively investigated, and its threedimensional structure has been published (35,42). The enzyme acts not only on PP but also on 4HPP to produce the corresponding aldehydes.…”
Section: Resultsmentioning
confidence: 99%
“…By virtue of the neutral ring in place of the positively charged thiazolium ring, the authors suggested that this would serve as an electrostatic mimic of the carbene [57,58]. Later the thiazolium ring was replaced by a triazole ring in yet a different mimic of a neutral 5-membered ring [59].…”
Section: The C2-carbanion/ylide/carbenementioning
confidence: 97%
“…The 3-deazaThDP synthesized by the Leeper group enabled observation of the MM complex with substrates in a E1p from Geobacillus stearothermophilus [57] and in indolepyruvate decarboxylase [58] and the residues important in maintaining the MM complex. On L. plantarum POX, there was significant concentration of LThDP found in the active centers [41] after acidification and precipitation of protein.…”
Section: The Michaelis Menten Complex (Mm)mentioning
confidence: 99%
“…In A. brasilense, the decarboxylase can use both indole-3-pyruvate and phenylpyruvate as substrates ). In addition, the crystal structure of both indole-3-pyruvate decarboxylases has been determined (Schütz et al 2003b;Versées et al 2007a;Versées et al 2007b). …”
Section: Indole-3-pyruvate Pathwaymentioning
confidence: 99%